2017
DOI: 10.4236/ape.2017.72017
|View full text |Cite
|
Sign up to set email alerts
|

After-School Physical Activity Interventions on Child and Adolescent Physical Activity and Health: A Review of Reviews

Abstract: Schools are a critical setting for children to accrue recommended levels of physical activity, and after-school programmes are suggested to supplement existing programmes such as physical education. This review of reviews provides a comprehensive picture of the effects of after-school physical activity programmes on student physical activity and health. We completed a literature search of electronic databases and identified six existing systematic reviews and meta-analyses of the effects of after-school progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 33 publications
3
45
1
Order By: Relevance
“…There is further need to design, implement, and provide supervised quality after-school interventions that target PA programs in diverse settings which may help adolescents to achieve daily PA recommendations. 50,51 Henceforth, comparison of adolescents according to their living areas such as rural, suburb and metropolis is recommended. It is also worth to mention that, precise estimation of PA with self-reported methods might have limit the validity among adolescents and do not provide adequate description of the intensity and duration of physical activity and self-report methods do not provide an opportunity to assess patterns of physical activity (i.e., bouts of activity) within a given day or over several days.…”
Section: Discussionmentioning
confidence: 99%
“…There is further need to design, implement, and provide supervised quality after-school interventions that target PA programs in diverse settings which may help adolescents to achieve daily PA recommendations. 50,51 Henceforth, comparison of adolescents according to their living areas such as rural, suburb and metropolis is recommended. It is also worth to mention that, precise estimation of PA with self-reported methods might have limit the validity among adolescents and do not provide adequate description of the intensity and duration of physical activity and self-report methods do not provide an opportunity to assess patterns of physical activity (i.e., bouts of activity) within a given day or over several days.…”
Section: Discussionmentioning
confidence: 99%
“…An umbrella review, composed of 6 systematic reviews (2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016), examining the effects of after-school programs on child and adolescent physical activity and health found there was only modest support of the benefits of after-school programs on physical activity levels. 5 Programs that were delivered within school settings twice or more per week showed greater potential in increasing children's physical activity; however, the breadth of factors influencing the effectiveness of after-school programs remained largely unknown. More research to understand what characterizes highquality after-school physical activity programs was recommended.…”
mentioning
confidence: 99%
“…Factors such as the use of theoretical frameworks and objective measures of physical activity and reporting the fidelity of interventions was suggested. 5 In addition to after-school programs focusing on increasing physical activity among children, studies have also reported other outcomes, such as academic enrichment. A meta-analysis examined the effects of after-school programs on personal and social skills, including academic performance.…”
mentioning
confidence: 99%
“…Demetriou et al examined 6 systematic reviews and meta‐analyses of the effects of ASPs on child and adolescent PA and health. They compared the reviews on numerous factors, including the databases searched, aims, outcome variables, PA measures, inclusion criteria, and the quality of the studies.…”
mentioning
confidence: 99%